Association between hamstring coactivation during isokinetic quadriceps strength testing and knee cartilage worsening over 24 months. Issue 6 (June 2022) - Murphy, M.T.; Wang, N.; Felson, D.T.; Nevitt, M.C.; Lewis, C.E.; Frey-Law, L.; Guermazi, A.; Segal, N.A.
Summary: Objective: This study aimed to determine longitudinal associations, including sex-specific differences, between greater knee flexor antagonist coactivation and worsening cartilage morphology in knees with or at risk for osteoarthritis (OA). Design: Baseline measurements were collected at the 60-month visit of a longitudinal osteoarthritis study following community-dwelling participants (MOST). Knee flexor and extensor muscle activity were measured with surface electromyography during a maximal isokinetic knee extension task. MRI analyzed knee cartilage morphology at baseline and 24-month follow-up. Multivariable adjusted logistic regression models were used to assess associations between coactivation level and cartilage morphology worsening. Results: Analysis of 373 women (mean ± SD age 67.4 ± 7.3 years and BMI 29.7 ± 5.0 kg/m 2 ) and 240 men (66.5 ± 7.8 years and 29.9 ± 4.5 kg/m 2 ) revealed that women had greater medial ( P < 0.001), lateral ( P < 0.001), and combined ( P < 0.001) hamstring coactivation than men. In both sexes, combined hamstring coactivation was associated with patellofemoral cartilage morphology worsening [1.23 (1.02, 1.49)] and to a less significant degree with whole knee cartilage morphology worsening [1.21 (0.98, 1.49)]. In men, greater combined hamstring coactivation was associated with increased risk for whole knee [1.59 (1.06, 2.39)] and patellofemoral [1.38 (1.01, 1.88)] cartilage morphology worsening and point estimates suggested association between medial hamstring coactivation and medial tibiofemoral cartilage morphology worsening. No significant associations were detected between greater hamstring coactivation and cartilage morphology worsening in women. Conclusions: These findings suggest a longitudinal relationship between antagonist hamstring coactivation during isokinetic knee extensor testing and worsening of cartilage morphology over 24 months in men with or at risk for knee OA.